2019
DOI: 10.1055/s-0039-1687863
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician Attitudes toward Digital Voice Assistant Technology Use in Clinical Practice

Abstract: Objective Digital voice assistant technology provides unique opportunities to enhance clinical practice. We aimed to understand factors influencing pediatric providers' current and potential use of this technology in clinical practice. Methods We surveyed pediatric providers regarding current use and interest in voice technology in the workplace. Regression analyses evaluated provider characteristics associated with voice technology use. Among respondents not interested in voice technology, we elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Once more, with this in mind, this study's results conform to several publications on the related idea of electronic systems and their impact on employees, particularly in hospitals, but by studying ve aspects of the system's process, this combination is somehow unique and entirely fruitful. As a result, while the descriptive and multiple regression analyses show that this study has unique results, it is still consistent with the literature, particularly [2,3,8,12,33]. Similarly, but with more clari cation, Liddy and colleagues [26] revealed that the electronic consultations of physicians globally are more useful.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Once more, with this in mind, this study's results conform to several publications on the related idea of electronic systems and their impact on employees, particularly in hospitals, but by studying ve aspects of the system's process, this combination is somehow unique and entirely fruitful. As a result, while the descriptive and multiple regression analyses show that this study has unique results, it is still consistent with the literature, particularly [2,3,8,12,33]. Similarly, but with more clari cation, Liddy and colleagues [26] revealed that the electronic consultations of physicians globally are more useful.…”
Section: Resultssupporting
confidence: 87%
“…As an example, some hospitals use digital voice assistants to facilitate communication between patients and healthcare providers. The system features that are more effective and easier to use contribute to user satisfaction and productivity [3]. The availability of electronic technologies for trimming, such as workpiece 3D metal printing offered with modern printing and programming, is an example of technological advancement these days.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to notice that Ref. [ 22 ] is presenting a study showing that currently only one-eighth of pediatric providers are using VA technology in their clinical setup, while 47.4% manifested their willingness in trying digital voice assistants. In [ 23 ], VAs are used to understand medication names in USA and Canada, but the researchers’ conclusion is that such kind of devices should not be used for the moment as a reliable source of medical information and guidance.…”
Section: Previous Workmentioning
confidence: 99%
“…Using the technology itself, however, has not stopped hospital researchers from exploring pediatric providers’ attitudes toward digital voice assistants in other US hospitals. The nationwide study found that only one eighth of respondents currently use this technology, while half of respondents were interested in trying voice technology in the future (Wilder et al, 2019).…”
Section: Resultsmentioning
confidence: 99%